Microcirculation function assessment in acute myocardial infarction: A systematic review of microcirculatory resistance indices - Silva, Marta; Paiva, Luis; Teixeira, Rogério; Ferreira, Maria João; Gonçalves, Lino (Frontiers in Cardiovascular Medicine, 2022)
Background Up to 50% of acute myocardial infarction (MI) patients present with microvascular dysfunction, after a successful percutaneous coronary intervention (PCI), which leads to worse clinical outcomes. The main purpose of this study is to provide a critical appraisal of the emerging role of invasive microvascular resistance indices in the MI setting, using the index of microcirculatory resistance (IMR), hyperemic microvascular resistance (HMR) and zero-flow pressure (Pzf). Methods We systematically explored relevant studies in the context of MI that correlated microcirculation resistance indices with microvascular dysfunction on cardiac magnetic resonance (CMR), microvascular dysfunction occurring in infarct related arteries (IRA) and non-IRA and its relation to clinical outcomes. Results The microcirculation resistance indices correlated significantly with microvascular obstruction (MVO) and infarct size (IS) on CMR. Although HMR and Pzf seem to have better diagnostic accuracy for MVO and IS, IMR has more validation data. Although, both IMR and HMR were independent predictors of adverse cardiovascular events, HMR has no validated cut-off value and data is limited to small observational studies. The presence of microvascular dysfunction in non-IRA does not impact prognosis. Conclusion Microvascular resistance indices are valuable means to evaluate microcirculation function following MI. Microvascular dysfunction relates to the extent of myocardial damage and clinical outcomes after MI. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021228432], identifier [CRD42021228432].